Instruments assessing attitudes toward or capability regarding self-management of osteoarthritis: a systematic review of measurement properties. Issue 8 (August 2017) - Eyles, J.P.; Hunter, D.J.; Meneses, S.R.F.; Collins, N.J.; Dobson, F.; Lucas, B.R.; Mills, K.
Summary: Objective: To make a recommendation on the "best" instrument to assess attitudes toward and/or capabilities regarding self-management of osteoarthritis (OA) based on available measurement property evidence. Methods: Electronic searches were performed in MEDLINE, EMBASE, CINAHL and PsychINFO (inception to 27 December 2016). Two reviewers independently rated measurement properties using the Consensus-based Standards for the selection of Health Measurement Instruments (COSMIN) 4-point scale. Best evidence synthesis was determined by considering COSMIN ratings for measurement property results and the level of evidence available for each measurement property of each instrument. Results: Eight studies out of 5653 publications met the inclusion criteria, with eight instruments identified for evaluation: Multidimensional Health Locus of Control (MHLC), Perceived Behavioural Control (PBC), Patient Activation Measure (PAM), Educational Needs Assessment (ENAT), Stages of Change Questionnaire in Osteoarthritis (SCQOA), Effective Consumer Scale (EC-17) and Perceived Efficacy in Patient–Physician Interactions five item (PEPPI-5) and ten item scales. Measurement properties assessed for these instruments included internal consistency ( k  = 8), structural validity ( k  = 8), test–retest reliability ( k  = 2), measurement error ( k  = 1), hypothesis testing ( k  = 3) and cross-cultural validity ( k  = 3). No information was available for content validity, responsiveness or minimal important change (MIC)/minimal important difference (MID). The Dutch PEPPI-5 demonstrated the best measurement property evidence; strong evidence for internal consistency and structural validity but limited evidence for reliability and construct validity. Conclusion: Although PEPPI-5 was identified as having the best measurement properties, overall there is a poor level of evidence currently available concerning measurement properties of instruments to assess attitudes toward and/or capabilities regarding osteoarthritis self-management. Further well-designed studies investigating measurement properties of existing instruments are required.